Antimicrobial Resistant Bacteria Isolated from Intensive Care Units - Eman Muftah Elzouki; Najah Ahmeda Ibrahim; Salwa Muftah Eljamay; Aisha M. Bojazyah (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
Aimed to determine the kind of microorganisms probably to be gifted inside the in-depth care unit and the suitable antibiotics for them. ‏Methods use the duration between October and December 2021‏. The samples had been carried from surfaces and in the ICUs of Al Wahada Hospital in Derna City Libya. ‏Result: The percent and the type of pathogenic agent isolated from intensive care units (ICU & CCU) the highest percent for gram-positive bacteria at 47%, then gram-negative at 19% and fungi at 7.0%, and the percent for there is no presence of pathogenic agent by 27% The bacterial spp, types, numbers, and that the highest percent for Gram-positive bacteria (Staphylococcus epidermidis.20 (39.22%) Staphylococcus aureus 29 (56.86%). As for the Gram-negative bacteria, the highest percentage for Klebsiella pneumonia is 8(40%), and Escherichia coli 9 (45%). As for the Fungi, Candida albicans 2(25%), Aspergillus flavus 6(75%). the surface which has the highest contamination with many types of bacteria were beds then tables, cabinets, and covers of baskets, NBG was the most common bacterium found on all surfaces, followed by S. epidermidis, S. aureus, E. coli, and K. pneumonia. Pseudomonas aeruginosa, S. epidermidis, and S. aureus were all drug resistant., as for Klebsiella pneumonia resistant to most of the antibiotics, Streptococcus spp resistant to many antibiotics except CTX, COL, CAZ, IMIP, which is sensitive, and Escherichia coli and resistant for rest of antibiotic. ‏The conclusion that Gram-negative bacteria are the most microorganisms that survive on different surfaces despite changes in environmental conditions which make them resistant to antibiotics.